Home is in between - Perkins, Mitali; Naidu, Lavanya (2021)
Immigrating to America, a young girl navigates between her family's Bengali traditions and her new country's culture.
Ages 4-8.
Grades K-1.
Keywords: Emigration and immigration -- Fiction; Immigrants -- Fiction; Bengali Americans -- Fiction; Home -- Fiction